Digital Literacy Skills and Foreign Language Anxiety of Gen Z in Malang: How Does It Correlate? - Margaretta, Iga Shevy; Rohmah, Zuliati; Degeng, Putu Dian Danayanti (Universitas Muhammadiyah Yogyakarta, 2024)
Digital technology now plays an important part in everyday life, requiring digital literacy skills. It also has significant effects on supporting educational needs, including foreign language learning. Some studies have revealed that learners with a high level of DLS will feel less anxious about joining the foreign language learning process. By implementing the quantitative approach, this study investigated the Digital Literacy Skills (DLS) and Foreign Language Anxiety (FLA) level of Gen Z in Malang as well as the correlation between DLS and FLA. Generation Z was chosen because they are known as digital natives. There were two questionnaires disseminated and were filled out by 100 Gen Z learners in Malang. DLS and FLA level of Gen Z in Malang were determined by finding the mean score while Pearson Correlation test was applied to determine the correlation between DLS and FLA. The results of this study suggested that Gen Z had a high level of DLS and moderate level of FLA Besides, there is weak correlation between DLS and FLA (Sig.2-tailed=0.004, Pearson Correlation=-0.486). Gen Z proved that they had a high DLS yet still experienced the FLA. Gen Z required direct assistance from educators rather than doing independent foreign language learning by employing their high DLS. Thus, combining face-to-face foreign language learning with digital technologies could assist Gen Z in reducing their FLA.